Effect of Supplemental Trace Mineral Source on Haircoat and Activity Levels in Senior Dogs - Laura A. Amundson; Allison A. Millican; Erik Swensson; Mike L. McGilliard; Dana Tomlinson (Animals)
Trace minerals (TMs) are pivotal for animal wellbeing and appearance. This study evaluated the effects of TM (Zn, Mn, Cu, and Fe) sources on senior dogs’ haircoat and activity. Dogs (mean age 9.16 yr) were fed a control diet (inorganic TM) for 14 d before being assigned to one of three treatments for 3 mo. Treatments included inorganic (Control; n = 10), amino acid-complexed (TMC; n = 17; ZINPRO® ZnMet + Zinpro® Availa® Mins) or lysine and glutamic acid-complexed (TMC-LG; n = 16; Zinpro® ProPath®) supplemental TM. Treatments were formulated to provide standard (Control—100 ppm Zn, 5 ppm Mn, 12 ppm Cu, 45 ppm Fe) or product-recommended (TMC and TMC-LG—100 ppm Zn, 25 ppm Mn, 7 ppm Cu, 45 ppm Fe) TM levels (DM basis). Hair length, regrowth, and shedding were measured along with activity. Dogs fed TMC (26.43 mm; 11.64 mm/mo) and TMC-LG (27.87 mm; 12.6 mm/mo) had significantly (p ≤ 0.05) longer hair that grew faster compared to the Control (18.93 mm; 9.14 mm/mo). At 3 mo TMC-LG-fed dogs had 0.38 g less shed hair, and TMC-fed dogs had 0.87 h more active time/d compared to the Control (p ≤ 0.05). Dogs fed TMC and TMC-LG had superior haircoat characteristics and activity compared to the Control.